Re-organising primary health care to respond to the Coronavirus epidemic in Cape Town, South Africa - Robert Mash; Charlyn Goliath; Gio Perez (AOSIS, 2020)
Cape Town is currently one of the hotspots for COVID-19 on the African continent. The Metropolitan Health Services have re-organised their primary health care (PHC) services to tackle the epidemic with a community-orientated primary care perspective. Two key goals have guided the re-organisation, the need to maintain social distancing and reduce risk to people using the services and the need to prepare for an influx of people with COVID-19. Facilities were re-organised to have 'screening and streaming' at the entrance and patients were separated into hot and cold streams. Both streams had 'see and treat' stations for the rapid treatment of minor ailments. Patients in separate streams were then managed further. If patients with chronic conditions were stable, they were provided with home delivery of medication by community health workers. Community health workers also engaged in community-based screening and testing. Initial evaluation of PHC preparedness was generally good. However, a number of key issues were identified. Additional infrastructure was required in some facilities to keep the streams separate with the onset of winter. Managers had to actively address the anxiety and fears of the primary care workforce. Attention also needed to be given to the prevention and treatment of non-COVID conditions as utilisation of these services decreased. The epidemic exposed intersectoral and intrasectoral fault lines, particularly access to social services at a time when they were most needed. Community screening and testing had to be refocused due to limited laboratory capacity and a lengthening turnaround time.